Tourism and postcolonialism : contested discourses, identities and representations - Hall, Colin Michael, 1961-; Tucker, Hazel, 1965- (Routledge/contemporary geographies of leisure, tourism, and mobility ;, 2004)
This book draws together theoretical and applied research in order to illuminate the links between tourism, colonialism and postcolonialism. Significantly, it aims to create a space for the voices of authors from postcolonial countries.